P159 Adapting the haddon matrix to incorporate one health for occupational health in animal agriculture. (1st September 2016) - Alexander, Bruce; Murphy, Darby; Bender, Jeffery
Abstract : The concept of One Health is widely used to address emerging and re-emerging infectious diseases. This concept focuses on the inextricable link between human, animal, and environmental health, and the interdisciplinary networks needed to address this interaction. Including and beyond infectious diseases of animal origin the One Health concept is well suited for developing models in occupational epidemiology where the worker's environment is linked to animals. Animal agriculture is one of the most hazardous industries where workers face risks of traumatic injury, respiratory hazards, and infectious diseases. Systems for raising animals for food have changed globally, which has fundamentally altered the interaction between workers and animals. The complex social, economic, and technical influences on agriculture requires a systematic and multidisciplinary approach toward evaluating worker health. We present an extension of the Haddon Matrix, to incorporate One Health aspects related to occupational health. The Haddon Matrix, developed for injury prevention and control, incorporates the agent, host, environment paradigm to include axes of pre-event, event, and post-event factors that are related to the person, the agent, the physical and the social environment. We extend this matrix to include a One Health component. For example, the most common cause of injury in dairy and swine production are interactions with animals, however these injuries do not all have the same aetiology and/or causal pathway. In these scenarios, the agent or vector of injury can be the animal, the environment, e.g. structure, or the worker. Social environment may include workplace safety culture, origin, social status and experience of the worker, economic determinants of animal production, and animal welfare concerns. When evaluating the causes and control of injury and other occupational hazards in animal agriculture, including zoonotic diseases, evaluating the complexity of the link between human, animal, and environmental is critical.